Literary Legacies of the Habsburg Empire in a Postcolonial Perspective The Example of Miroslav Krleža - Car Prijić, Milka (Array, 2014)
The perspective postulated in the title of this essay focuses on the peripheral, South-Slav areas of the Habsburg Empire. This essay circumvents the debate on the extent of colonialism, i.e. it does not aim at an extensive description of the historical conditions in the Habsburg Monarchy, in favour of providing an answer to another question – the question regarding the alarming situation in the final phase of the “k. und k.” Monarchy, raised by Miroslav Krleža in his essays.